Bracing Connections for Heavy Construction - Thornton, William A. (Engineering Journal, 1984)
The design of complex connections is not an exact science. Over the years, an intuitive approach to connection design has become widely accepted. This approach is based on the idea the structure (and parts thereof) will behave as the designer dictates, if he provides a path of adequate strength for the load (or loads) to follow. This "adequate strength path" is determined from the principles of statics and strength of materials. About 30 years ago, this intuitive load path method of design was put on a rigorous basis with the development of the Theorem of Limit Analysis—specifically the Lower Bound Theorem of Limit Analysis, which states: if a distribution of forces in the structure can be found which is in equilibrium with the applied loads, and if these forces everywhere within the structure are of such a magnitude that the yield stress (or yield criterion) is nowhere exceeded, then the applied loads are less than, or at most equal to, the loads required for collapse (unbounded yield deformations) to occur. Thus, if a load path is provided, the elements of which are in equilibrium with the applied loads, and if the stresses in these elements nowhere exceed the yield stress, a safe design will have been achieved. Also, the relative stiffness of the various connection elements should be considered in order to minimize the possibility of fracture.